2010
DOI: 10.1038/nsmb.1887
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mechanism of ABA receptor antagonism

Abstract: The phytohormone abscisic acid (ABA) functions through a family of fourteen PYR/PYL receptors, which were identified by resistance to pyrabactin, a synthetic inhibitor of seed germination. ABA activates these receptors to inhibit type 2C protein phosphatases, such as ABI1, yet it remains unclear whether these receptors can be antagonized. Here we demonstrate that pyrabactin is an agonist of PYR1 and PYL1, but unexpectedly an antagonist of PYL2. Crystal structures of the PYL2–pyrabactin and PYL1–pyrabactin–ABI1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 35 publications
2
165
0
3
Order By: Relevance
“…GST-tagged PYL1 (∼51 kD) and PYL2 (∼46 kD) were pulled down by His-tagged PYL13 (∼22 kD) in an ABAindependent manner ( Figure 5C). Previous structural and biochemical investigations demonstrated that several PYLs (such as PYR1, PYL1, PYL2, PYL3) form homodimers in solution and that the dimer formation is important in regulating ABA binding and PP2C interactions [5,8,11,27,28,36,37]. Our results suggest that PYL13 can form heterodimers with other PYLs.…”
Section: Pyl13 Interacts With and Antagonizes Other Pylsmentioning
confidence: 58%
See 1 more Smart Citation
“…GST-tagged PYL1 (∼51 kD) and PYL2 (∼46 kD) were pulled down by His-tagged PYL13 (∼22 kD) in an ABAindependent manner ( Figure 5C). Previous structural and biochemical investigations demonstrated that several PYLs (such as PYR1, PYL1, PYL2, PYL3) form homodimers in solution and that the dimer formation is important in regulating ABA binding and PP2C interactions [5,8,11,27,28,36,37]. Our results suggest that PYL13 can form heterodimers with other PYLs.…”
Section: Pyl13 Interacts With and Antagonizes Other Pylsmentioning
confidence: 58%
“…Several of the PYLs have been shown to bind and inhibit clade A protein phosphatase type 2Cs (PP2Cs, comprising ABI1, ABI2, HAB1, HAB2, AHG1, PP2CA, HAI1, HAI2, and HAI3) in the presence of ABA [2-4, 6, 7]. Structural studies confirmed that the PYLs are ABA receptors and showed that the PP2Cs can function as coreceptors because they enhance the ABA-binding affinities of the PYLs [5,[8][9][10][11]. In Arabidopsis protoplasts, PYR1 and PYLs 1-12 could release ABI1 inhibition of ABA-dependent activation of RD29B-LUC expression by the SnRK2 protein kinases such as OST1/SnRK2.6 [4].…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, it qualifies as a hypermorphic mutation in the presence of ABA and a PYR/PYL receptor, although paradoxically, hab1 G246D as well as abi1 G180D and abi2 G168D proteins, have a lower specific activity as compared to wt in the absence of ABA. [20,21,22,38]. Additionally, these studies reveal that whereas pyrabactin is an ABA-agonist for some PYR/PYL/RCAR receptors, e.g.…”
Section: Abi1-1 G180d Abi2-1 G168d and Hab1 G246d Hypermorphic Enzymesmentioning
confidence: 82%
“…A high degree of structural similarity is evident from the superposition of the three structures (Fig. 2), however, recent works using the pyrabactin molecule reveal subtle differences among the receptor binding pockets with important functional consequences, since pyrabactin is an agonist of PYR1 and PYL1, whereas it is an antagonist of PYL2 [20,21,22]. Different experimental data indicate that these receptors exist as dimers in solution, however, the receptor-PP2C complexes have a 1:1 stoichiometry, implying that the receptor dimers have to dissociate before interacting with the PP2C [17,18,19].…”
Section: The Structure Of Pyr/pyl/rcar Receptorsmentioning
confidence: 97%
See 1 more Smart Citation